2009
DOI: 10.1002/app.31099
|View full text |Cite
|
Sign up to set email alerts
|

Properties and structural characterization of oxidized starch/PVA/α‐zirconium phosphate composites

Abstract: Two series of composites, i.e., polyvinyl alcohol (PVA)/oxidized starch (OST)/exfoliated a-zirconium phosphate (POST-ZrPn) and PVA/starch (ST)/exfoliated a-zirconium phosphate (PST-ZrPn), were fabricated using a casting and solvent evaporation method. The composites were characterized by Fourier transform infrared spectroscopy (FT-IR), thermal gravimetric analysis (TGA), differential scanning calorimetry (DSC), wide-angle X-ray diffraction (XRD), scanning electron microscopy (SEM), tensile testing, and moistur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…It indicated that SP interacted with polymers matrix, and the hydrogen bonding between PVA and CS was partially destructed. A quite similar tendency was reported for exfoliated a-zirconium phosphate introducing into the PVA/starch matrix [9]. It can also be seen that the elongation at break of nanocomposites increased with an increase in SP loading from 0 to 2 wt %, while the 2D clay platelet leads to the drastic decrease in the elongation at break of the resulting composites at high loading [5].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…It indicated that SP interacted with polymers matrix, and the hydrogen bonding between PVA and CS was partially destructed. A quite similar tendency was reported for exfoliated a-zirconium phosphate introducing into the PVA/starch matrix [9]. It can also be seen that the elongation at break of nanocomposites increased with an increase in SP loading from 0 to 2 wt %, while the 2D clay platelet leads to the drastic decrease in the elongation at break of the resulting composites at high loading [5].…”
Section: Resultssupporting
confidence: 80%
“…The contact angle (CA) of a liquid on the film surface was measured using a Kruss DSA 100 (Kruss, Hamburg, Germany) apparatus at ambient temperature. The moisture uptake (MU) of the samples was determined at RH of 76% by the method of Yang et al [9].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, in the POST-ZrPn series, rb and eb increase with an increase in a-zirconium phosphate (a-ZrP) loading; however, higher a-ZrP loads resulted in the aggregation of a-ZrP particles. Compared with POST-ZrP0, the values for rb, eb, and water resistance of POST-ZrP3, containing 1.5 wt % a-ZrP, are increased by 128.8%, 51.4%, and 30.2%, respectively [102]. [103].…”
Section: Inorganic Organic Composite Membranementioning
confidence: 96%
“…Both tensile strength and water resistance were improved. Yang et al (2010) fabricated oxidized starch/PVOH/exfoliated ␣-zirconium phosphate (␣-ZrP) composites using a solution casting method. ␣-ZrP exhibits great advantages over MMT clay, including a much higher purity and surface energy, ease of intercalation, and ease of exfoliation.…”
Section: Starch-pvoh Based Nanocompositesmentioning
confidence: 99%